Spodoptera eridania: current and emerging crop threats from another invasive, pesticide-resistant moth - Weinberg, J.; Ota, N.; Goergen, Georg E.; Fagbohoun, J.R.; Tepa-Yotto, G.; Kriticos, D.J. (Schweizerbart, 2022)
Spodoptera eridania (Stoll), a polyphagous lepidopteran pest from the Americas, has recently invaded western and central Africa. Like its congeners, S. eridania has developed pesticide resistance. The rapid global spread and impacts of Spodoptera frugiperda (J.E. Smith) has raised concerns about whether S. eridania is set to do the same. Here we fit a CLIMEX niche model for S. eridania and apply a climate change scenario for 2050 to investigate the sensitivity of the pest threat. We find that S. eridania can potentially expand its range throughout the tropics and into the sub-tropics, threatening a range of important commercial and subsistence crops. An important feature of the pest threat posed by S. eridania is the extent of its ephemeral habitat during warmer months. Modelled climatic changes will mostly expand this species potential range poleward by around 200 km by 2050, indicating a moderate sensitivity. These areas of emerging potential expansion are mostly into subtropical climates, supporting diverse cropping systems, including at risk crops beans, groundnut, potato, soybeans, tomato and sweet potato. The potential distribution of S. eridania in the Amazon basin and the southern boundary of the Sahara Desert appear set to contract substantially due to increasing heat stress. While it may not be as invasive as some of its congeners, nor acquire pesticide resistance as readily, S. eridania does have some of these traits, and the current and emerging pest threat posed by this moth deserves closer attention, especially in relation to intercontinental phytosanitary measures to slow its spread.